Nivolumab and Ipilimumab in the Treatment of Metastatic Uveal Melanoma: A Single-Center Experience - Vidhya Karivedu; Ihab Eldessouki; Ahmad Taftaf; Zheng Zhu; Abouelmagd Makramalla; Nagla Abdel Karim (Case Reports in Oncological Medicine, 2019)
Background. Metastatic uveal melanoma (MUM) is associated with a poor prognosis, with a median overall survival (OS) of 4–15 months. Despite new insights into the genetic and molecular background of MUM, satisfactory systemic treatment approaches are currently lacking. The study results of innovative treatment strategies are urgently needed. Patients and Methods. This was a retrospective case series of 8 patients with MUM managed at the University of Cincinnati between January 2015 and January 2018. The immune-related Response Evaluation Criteria in Solid Tumors (irRECIST) 1.1 criteria were used for patient evaluation, and magnetic resonance imaging was used for evaluation at treatment checkpoints. Objective. To assess the clinical outcome of patients with MUM treated with a combination of checkpoint inhibitors. Results. The series included eight patients, six men and two women, with MUM. Their median age at MUM diagnosis was 69 (range, 55–77) years. All patients were treated with ipilimumab and nivolumab combination along with transarterial chemoembolization (TACE), followed by nivolumab maintenance and monthly TACE procedures. The majority of patients had a partial response or stable disease. Two of the patients had partial response, while four others had stable disease. Two other patients experienced disease progression. Conclusion. We report the outcomes of eight patients with MUM treated with the combination of ipilimumab and nivolumab. We report the clinical outcome and toxicity associated with this treatment approach. Further studies are warranted to explore immunotherapy in MUM. These findings support the consideration of immunotherapy in MUM.